Las bibliotecas en el cine. Aportes para el análisis de la representación de las bibliotecas en el cine - Martín Otegui, Virginina (Revista General de Información y Documentación, 2009)
The first part of this work is a theoretical analysis of aspects of films –such as representation or narrative– that contribute to the make up of the library as it is represented in films. This space becomes a theoretical basis that responds methodologically to work on reading and analysis and to a selection of authors that cover different views of the topic. The second part analyses images of libraries in different films. The films were selected from viewing them and applying a narrative criterion oriented towards the role of the library within each film. The analysis considers each film from the presence of a library in it and focuses on the treatment of this space that the director makes and, in many cases, on the dialogues that occur in different scenes. The search for conclusions is done from recurrences and distinctions in the different representations.
Keywords: Libraries; Films; Social representation; Social imaginary